Implementasi E-Government di Kantor Desa Mekar Sari Kecamatan Kumpeh Kabupaten Muaro Jambi - Sarah Dwi Salsabilah; Hendriyaldi Hendriyaldi; Try Syeftiani (Journal Economic Excellence Ibnu Sina, 2025)
This research aims to examine the implementation of E-Governmentas well as the supporting and inhibiting factors in the implementation of E-Governmentat the Mekar Sari Village Office, Kumpeh District, Muaro Jambi Regency. This study employs a qualitative approach. The results of the research found that there are six dimensions in the implementation of E-Government, namely Data Infrastructure, Legal Infrastructure, Institutional Infrastructure, Human Infrastructure, Technology Infrastructure, and Strategic Thinking and Leadership. In Mekar Sari Village, the implementation of E-Governmentis quite good; however, there are still shortcomings in Human Infrastructure, particularly regarding community human resources who do not yet understand how to use the Open SID website. Additionally, in Technology Infrastructure, there are still limited facilities due to a lack of budget